The Effect Of Estrogen On The Male Reproductive System Of Rats Receiving Cimetidine - Ali Hammodi; Sajeda Al-Chalabi; Rana A. Asem (College of Education for Pure Sciences, 1999)
Abstract To show if a small dose of estrogen can interfere with the effect of Cimetidine on male reproductive system. Five groups of five randomly selected adult male rats were utilized. Rats were given food (laboratory rat chow) and water ad libitum. Rats were treated orally with Cimetidine 50mg/kg and subcutaneous injection with estradiol 0.01µg for 60 days. The animals were grouped as: group1, treated from days 1-10. Group2, treated from days 20-30. Group3, treated from days 40-50. Group4, treated from days 50-60. Group 5 received no treatment as a control group. Blood samples were taken from the eyes (by using capillary tubes) to measure testosterone (T) and follicular stimulating hormone (FSH) levels. Measurement of weights of the reproductive organs including the testis, epididymis (head, body, and tail), seminal vesicle and prostate were done. Body weight for each animal was recorded before and after treatment. Also we counted the total sperm count and the percentage of dead and alive spermatozoa for the treated groups using Eosin-negrosin stain. The testis weight and prostate weight was significantly increased in both groups 3 and 4, while seminal vesicle weight was significantly reduced. FSH levels were significantly increased, while testosterone levels were unchanged. Total sperm count and a number of a live sperms were significantly reduced and the number of dead sperms was significantly increased among the treated groups. Cimetidine has hazards on male reproductive function while estrogen didn't play any role to abolish this action.